Nutrition regulates sex expression in a gender diphasy plant, Lilium concolor var. megalanthum - Chen, Xin; Wang, Lei; Yan, Xingfu; Tang, Zhanhui (Frontiers in Plant Science, 2023)
The evolution and maintenance of plant polymorphism have always received much attention. Gender diphasy is a rare sexual system. Plant individuals with gender diphasy can adjust the resource allocation of different functional organs according to the changes of environmental conditions to regulate the sex expression of individuals, and the sex expression can be converted between years. However, our understanding of sex expression in plants is still very insufficient. In this study, we explored whether the perennial plant Lilium concolor var. megalanthum has a gender diphasy system and whether environmental resource availability affects its resource allocation and sex expression.Method: By collecting the bulbs of two sexual phenotypes (male and hermaphrodite) in the field and simulating the application of different levels of nutrients under the same habitat conditions, the growth and reproduction indexes and sex expression of plants in two years (2021 and 2022) were measured to evaluate the resource allocation strategy and sex expression pattern of Lilium concolor var. megalanthum.We found that the sex expression of Lilium concolor var. megalanthum was variable in continuous years. Under limited resources, Lilium concolor var. megalanthum increases the biomass resources of the leaves and has a longer flowering period. Resource availability regulates the growth, This is a provisional file, not the final typeset article reproduction and sex expression of Lilium concolor var. megalanthum. Bulb size is the main factor affecting its growth, reproduction and sex expression after accumulating sufficient resources.Discussion: This study confirms that Lilium concolor var. megalanthum has gender diphasy system. There is a strong trade-off between growth and reproduction under limited resources. Nutrient levels can regulate the reproduction and sex expression process of Lilium concolor var. megalanthum. With the growth of Lilium concolor var. megalanthum in consecutive years, the size dependence of bulbs may be the decisive factor in its sex expression.